A study on the performance of the convenience stores (c-store) of Esso Malaysia Berhad / Anizah Zainuddin - Zainuddin, Anizah (1992)
Convenience Store shopping is certainly making its mark in Malaysia. Esso Malaysia Berhad have come the long way and tried to fulfill their customers by operating " Food Store " or C-Store at all their new Esso Service Stations. To date, Esso Malaysia Berhad has 26 C-Stores throughout the country and expects to have 35 in operation by the end of 1992. In an attempt to find out whether C-Store attracts customers to the service stations, a study was' carried out in the form of collecting Statistical data on the fuel sales and C-Store sales, from June 1990 till June 1992. Written questionnaire was also carried out which includes question about the effectiveness of the C-Store to the customer's point of view.